Karakteristik pasien retinopahty of prematurity (ROP) - Ratih Natasha Maharani; Sri Irmandha Kusumawardhani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Retinopathy of prematurity (ROP) is a leading cause of irreversible visual impairment in infants, particularly premature infants. ROP occurs due to incomplete vascularization in premature infants. ROP screening is an initial strategy to prevent blindness from ROP. Purpose: To describe the characteristics of patients with retinopathy of prematurity (ROP). Method: This multicenter, retrospective, observational study, using medical records of patients diagnosed with ROP based on the International Classification of Diseases (ICD)-10 code H35.1, was conducted at 10 hospitals in Makassar City between January 2020 and December 2022. Data were collected from the history and physical examination available in the medical records. The diagnosis of ROP was confirmed based on retinal camera images using the Three 3 Nethra Neo Digital Widefield Imaging System. Results: The incidence of ROP in Makassar City from January 2020 to December 2022 was 14.87%. Most patients had a history of preterm birth between 28 and 33 weeks, with a birth weight of less than 1500 grams (39.3%). The majority of respondents had a history of oxygen supplementation (78.0%), along with other risk factors such as sepsis, multiple pregnancies, a history of transfusion, phototherapy, or a history of apnea. Ninety-eight patients had ROP in both eyes, with the most common stage at the first visit being stage 3 (37.0%). The most common treatment modality for these patients was laser photocoagulation (24.4%). Conclusion: ROP screening activities have yielded positive results, allowing for more timely diagnosis of ROP in preterm infants and prompt treatment. Suggestion: Further research is needed to identify risk factors significantly associated with ROP incidence and treatment prognosis. Keywords: Characteristics; Retina; Retinopathy of Prematurity (ROP); Visual Impairment. Pendahuluan: Retinopathy of prematurity (ROP) merupakan penyebab utama gangguan penglihatan yang ireversibel pada bayi, khususnya bayi prematur. ROP terjaid akibat adanya gangguan vaskularisasi yang komplit pada bayi prematur. Skrining ROP merupakan strategi awal untuk mencegah kebutaan akibat ROP. Tujuan: Untuk memaparkan karakteristik pasien dengan retinopathy of prematurity (ROP). Metode: Penelitian observasional deskriptif retrospektif multisenter dengan mengambil data rekam medis pasien di beberapa rumah sakit tempat dilakukan skrining ROP yang terdiagnosis ROP berdasarkan kode diagnosis International Classification Code (ICD)-10 H35.1, dilakukan di 10 rumah sakit di Kota Makassar, pada periode bulan Januari 2020–Desember 2022. Data diambil berdasarkan anamnesis dan pemeriksaan fisik yang ada dalam rekam medis. Diagnosis ROP ditegakkan berdasarkan foto hasil pemeriksaan retinal camera menggunakan Three 3 Nethra Neo Digital Wide Field Imaging System. Hasil: Insiden ROP di Kota Makassar periode Januari 2020 – Desember 2022 sebesar 14.87%. Sebagian besar pasien memiliki riwayat kelahiran prematur pada rentang 28–33 minggu dengan berat lahir kurang dari 1500 gram sebanyak 39.3%. Mayoritas responden memiliki riwayat penggunaan suplementasi oksigen sebesar 78.0%, disertai dengan faktor risiko lain, seperti sepsis, gemelli, riwayat transfusi, fototerapi, atau riwayat apnea. Sebanyak 98.8% pasien mengalami ROP pada dua mata dengan stadium terbanyak pada kunjungan pertama adalah stadium 3 dengan persentase 37.0%. Modalitas terapi yang banyak dilakukan pada pasien adalah laser fotokoagulasi (24.4%). Simpulan: Kegiatan skrining ROP yang telah dilakukan memberikan hasil yang baik, sehingga bayi prematur dapat lebih cepat terdiagnosis ROP dan segera diberikan tindakan. Saran: Penelitian lebih lanjut diperlukan untuk dapat melihat faktor risiko yang secara signifikan berhubungan dengan kejadian ROP serta prognosis dari tatalaksana yang telah diberikan. Kata Kunci: Gangguan Penglihatan; Karakteristik; Retina; Retinopathy of Prematurity (ROP).